Extensive chromosomal rearrangements and rapid evolution of novel effector superfamilies contribute to host adaptation and speciation in the basal ascomycetous fungi. (8th January 2020) - Wang, Qinhu; Sun, Manli; Zhang, Yimei; Song, Zhenzhen; Zhang, Shijie; Zhang, Qiang; Xu, Jin‐Rong; Liu, Huiquan
Abstract: The basal ascomycetes in genus Taphrina have strict host specificity and coevolution with their host plants, making them appealing models for studying the genomic basis of ecological divergence and host adaption. We therefore performed genome sequencing and comparative genomics of different Taphrina species with distinct host ranges to reveal their evolution. We identified frequent chromosomal rearrangements and highly dynamic lineage‐specific (LS) genomic regions in Taphrina genomes. The LS regions occur at the flanking regions of chromosomal breakpoints, and are greatly enriched for DNA repeats, non‐core genes, and in planta up‐regulated genes. Furthermore, we identified hundreds of candidate secreted effector proteins (CSEPs) that are commonly organized in gene clusters that form distinct AT‐rich isochore‐like regions. Nearly half of the CSEPs constitute two novel superfamilies with modular structures unique to Taphrina . These CSEPs are commonly up‐regulated during infection, enriched in the LS regions, evolved faster, and underwent extensive gene gain and loss in different species. In addition to displaying signatures of positive selection, functional characterization of selected CSEP genes confirmed their roles in suppression of plant defence responses. Overall, our results showed that extensive chromosomal rearrangements and rapidly evolving CSEP superfamilies play important roles in speciation and host adaptation in the early‐branching ascomycetous fungi. Abstract : The basal ascomycetes in genus Taphrina have strict host specificity and coevolution with their host plants. This work addressed the genomic determinants of host adaptation for Taphrina pathogens.